No alternative for Swedish teachers? The recontextualisation of discourses of teacher professionalism in Social Democrat-Green Party coalition policy - Milner, Alison (2015)
Sweden is faced with a teacher recruitment and retention crisis. In an attempt to attract more to the profession, the newly elected Social Democrat-Green Party coalition claims to promote an alternative discourse of teacher professionalism to that of its centre-right predecessor. Yet, government policy is formulated within the wider context of cultural and economic globalization and, as a minority government, the red-green coalition must gain the consent of the opposition to implement policy, and both teachers and the wider electorate to attain political legitimacy. Given the immediacy of events, there is no qualitative research which examines this alleged discursive shift at policy level and its link to power relations. This critical, interpretive study explores the continuities, changes and contradictions within discourses of teacher professionalism in Sweden, and how they might be used to further social, economic and political interests. A Faircloughian (2010) Critical Discourse Analysis was conducted on a sample of seven documents; six written policy manifestos from the Social Democrats and the Green Party, and one audio-visual speech by the current Minister for Education, Gustav Fridolin. Analysis was conducted at text, discourse practice and social practice level with the use of linguistic and political theory to examine the interdiscursivity of texts. Beyond the recontextualisation of discourses of managerial professionalism and its resultant bureaucratization of teachers’ work, this study reveals that neoliberal ideologies continue to permeate discourses through government attempts to define teacher subjectivities. Even so, within the discourse, there is space for teachers to reject these interpretations. Although limited in scale, the findings raise important issues for teachers, trade unions and policymakers; they reveal how occupational control and change is implicit within discourses of teacher professionalism, yet problematic without the consent of the most important social actors. Arguably, in a decentralized education system, further research is required to compare national policy discourses with those construed by municipalities and free schools, to investigate how these multiple discourses are interpreted and inculcated by teachers, and examine which counter-hegemonic discourses are available to the profession.